Efikasi berbagai campuran bahan aktif herbisida terhadap gulma Stenochlaena palustris di perkebunan kelapa sawit - Edyson Edyson; Fitrah Murgianto; Adhy Ardiyanto (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2021)
Weeds are one of the limiting factors in oil palm cultivation. One of the most dangerous weeds in oil palm plantations is Stenochlaena palustris. This weed generally grows and develops in the lowlands, which contain lots of water. This study aimed to determine the combination of active ingredients and herbicide concentrations that effectively control S. palustris. This research used a randomized block design (RBD) with eight treatments of the active herbicide in 15 liters of water, namely methyl metsulfuron 5 g + ammonium glufosinate 50 ml, methyl metsulfuron 10 g + ammonium glufosinate 50 ml, methyl metsulfuron 2.4 g + triclopyr mix and aminopyralid potassium 45 ml + adjuvant 15 ml, methyl metsulfuron 2.4 g + mix triclopyr and aminopyralid potassium 60 ml + adjuvant 15 ml, methyl metsulfuron 10 g + ammonium glufosinate 30 ml + sulfentrazone 10 ml, methyl metsulfuron 6.6 g + glyphosate 66 ml, 5 g methyl metsulfuron + 50 ml glyphosate, and 100 ml glyphosate + 5 g saflufenacil with three replications. Observation data was carried out by analysis of variance and followed by the least significant difference test (LSD) at the 95% confidence level. The results showed a mortality rate of 100% in the treatment of methyl metsulfuron 10 g + ammonium glufosinate 30 ml + sulfentrazone 10 ml had been achieved in 3 weeks after application so that this treatment was the most effective in controlling S. palustris with rapid death and the re- long growth. Keywords: herbicides, oil palm, Stenochlaena palustris, weed